2013
DOI: 10.1111/ajd.12100
|View full text |Cite
|
Sign up to set email alerts
|

IgG4‐related disease with cutaneous manifestations treated with rituximab: Case report and literature review

Abstract: Immunoglobulin type gamma 4 (Ig)G4-related disease (IgG4-RD) is a relatively recently described clinical entity characterised by elevated levels of serum IgG4 and tissue infiltration of IgG4+ plasma cells in various organ systems. Cutaneous involvement is rare but is becoming increasingly appreciated; typically presenting as erythematous papules and/or nodules that are commonly pruritic. We report a case of IgG4-RD presenting with persistent pruritic papules and unilateral parotid swelling. His serum IgG4 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
1
15
0
2
Order By: Relevance
“…1b).IgG4-related disease is a newly described systemic, autoimmune, fibro-inflammatory condition that can present with cutaneous features, with recent reports demonstrating the effectiveness of multiple agents including oral steroids, mycophenolate mofetil, azathioprine, methotrexate, thalidomide and rituximab. 1,2,3,4,5 Our case complements that of Jalilian and colleagues and again demonstrates a late diagnosis after a previous parotidectomy, possibly because the condition was not well described when the patient initially presented.…”
supporting
confidence: 77%
“…1b).IgG4-related disease is a newly described systemic, autoimmune, fibro-inflammatory condition that can present with cutaneous features, with recent reports demonstrating the effectiveness of multiple agents including oral steroids, mycophenolate mofetil, azathioprine, methotrexate, thalidomide and rituximab. 1,2,3,4,5 Our case complements that of Jalilian and colleagues and again demonstrates a late diagnosis after a previous parotidectomy, possibly because the condition was not well described when the patient initially presented.…”
supporting
confidence: 77%
“…Cutaneous involvement is rare but becomes increasingly appreciated, and Yamada and colleagues have reported that 6.3% of IgG4‐RD patients had cutaneous involvement . Skin lesions in IgG4‐RD typically present as erythematous papules and/or nodules that are commonly pruritic . It might be true that lung and/or skin can be the first target organs in patients with IgG4‐RD, but it is difficult, as well as challenging, to make the definitive diagnosis before the manifestations in other commonly‐affected organs such as the pancreas .…”
Section: Discussionmentioning
confidence: 99%
“…11 Conventional steroid-sparing agents like mycophenolates, azathioprine, or methotrexate have all been used in treatment of IgG4-RD, but no case series or clinical trials supporting their efficacy and long-term outcomes exist. 12 Although limited studies available, radiotherapy has been suggested to be effective in steroid refractory IgG4-ROD. 13 Rituximab, a monoclonal antibody directed against the B lymphocytic-specific antigen CD20, might target the subset of plasma cells that can produce IgG4 antibodies in cases of IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%